Sailing routes in the world of computation : 14th Conference on Computability in Europe, CiE 2018, Kiel, Germany, July 30-August 3, 2018, Proceedings /: 14th Conference on Computability in Europe, CiE 2018, Kiel, Germany, July 30-August 3, 2018, Proceedings. (2018) - Unknown
No abstract available